Implementation of the Scientific Debate Method to Improve the Speaking Skills of Students in the Arabic Language Education Program at Hasyim Asy’ari University - El-Harrani, Hayat Qoys; Kholis, Ahmad Nur (Global Education Journal, 2025)
Speaking skills (maharah al-kalam) are a key competency in Arabic language learning, essential not only for daily communication but also for academic contexts such as scientific debates. However, many students in the Arabic Language Education Program (PBA) at Hasyim Asy’ari University face challenges including limited vocabulary, insufficient practice, grammatical errors, and low self-confidence in presenting arguments. This study aimed to describe the implementation of the scientific debate method in teaching speaking skills, identify obstacles encountered, and explore effective improvement strategies. Using a qualitative approach with a descriptive design, the research was conducted with fourth-semester students and a speaking skills lecturer in PBA UNHASY. Data were collected through direct observation, in-depth interviews, and documentation, using observation and interview guides as well as documentation formats. Analysis followed Miles and Huberman’s interactive model of data reduction, display, and conclusion drawing, with validity ensured through source and method triangulation. Findings show that the scientific debate method significantly improved students’ fluency, accuracy, vocabulary variety, self-confidence, and ability to present logical arguments. Challenges included vocabulary limitations, nervousness, lack of extracurricular practice, and difficulty in quick argument formulation. Effective strategies comprised providing thematic vocabulary lists, repeated practice with varied topics, constructive feedback, and academic-style debate simulations. The study concludes that integrating scientific debates into the curriculum fosters linguistic, cognitive, and affective development, and recommends consistent application supported by structured materials and extended implementation across institutions.